Immune System Acts on Orthodontic Tooth Movement: Cellular and Molecular Mechanisms. (25th October 2022) - Gao, Yajun; Min, Qingqing; Li, Xingjia; Liu, Linxiang; Lv, Yangyang; Xu, Wenjie; Liu, Xudong; Wang, Hua
Abstract : Orthodontic tooth movement (OTM) is a tissue remodeling process based on orthodontic force loading. Compressed periodontal tissues have a complicated aseptic inflammatory cascade, which are considered the initial factor of alveolar bone remodeling. Since skeletal and immune systems shared a wide variety of molecules, osteoimmunology has been generally accepted as an interdisciplinary field to investigate their interactions. Unsurprisingly, OTM is considered a good mirror of osteoimmunology since it involves immune reaction and bone remolding. In fact, besides bone remodeling, OTM involves cementum resorption, soft tissue remodeling, orthodontic pain, and relapse, all correlated with immune cells and/or immunologically active substance. The aim of this paper is to review the interaction of immune system with orthodontic tooth movement, which helps gain insights into mechanisms of OTM and search novel method to short treatment period and control complications.